A method for connected word recognition - GROCHOLEWSKI, S. (Archives of Acoustics, 1992)
In this paper, the description of the method for connected word recognition derived from the algorithm introduced by Vintsyuk is illustrated by means of a hypothetical example. Such a detailed presentation of the method should be useful from the practical point of view. The cited results of the real experiments confirm the ability of the method to perform reliable connected word recognition.